VD_FINDINFO Jug / 2025 / 277 vom 6. Dezember 2024 - VD Tribunal cantonal (2024)
MENACEDROIT PÉNAL, TENTATIVE SIMPLE | 126 al. 1 CP, 126 al. 2 CP, 180 al. 1 CP, 180 al. 2 let. a CP, 180 al. 2 let. b CP, 22 ad 180 CP